Parental Educational Level As A Predictor Towards The Return Rate Of Pre-Primary and Primary Pupils To School Amidst Coronavirus Pandemic in Port Harcourt Metropolis, Nigeria - Anero, Nnamdi; Okankwu, Elizabeth Amini (Advances in Social Sciences Research Journal, 2020)
The study was carried out to determine the extent parental educational levels predict return rate of pre-primary and primary pupils by parents as soon as the schools resume at the end or close to the end of coronavirus pandemic. The study which was carried in Port Harcourt, Nigeria adopted accidental sampling technique to sample 942 parents out of a population of 476,658 parents. Four research questions guided the study. The major instrument for the study was the Researchers made questionnaire titled “Return of children to school by parents amidst coronavirus pandemic”. The data generated was analyzed using simple percentage. Findings showed that parents whose educational levels were within non-completion of primary school education and Diploma certificates will return their children on the ground that schools can effectively administer hand washing by pupils while those with first degrees to the terminal degrees disagreed with the ability of schools to carry out a hand wash exercise. However, the parents generally agreed that the schools cannot maintain the required social distancing and administer frequent fluid intake to pupils as preventive measures and as a result would not return their children to schools. Based on these findings, the study among other things recommended thus: since some category of parents agree that the schools cannot enforce hand wash by children, NGO’S and public spirited individuals need to enlighten the schools on the need to take the business of hand wash serious; since the schools cannot maintain adequate spacing, the government and her agencies must urge the schools to operate two to three shifts so as to have adequate space and facilities that would enable them maintain the recommended social or physical distancing and that any school that will operate, must have a source of portable water confirmed by National Agency for Food and Drug Administration and Control (NAFDAC).